Case report: Identification of a novel heterozygous germline ERCC2 mutation in a patient with dermatofibrosarcoma protuberans - Zhang, Qing; Ju, Yongzhi; You, Xia; Sun, Tingting; Ding, Yi (Frontiers in Oncology, 2022)
Dermatofibrosarcoma protuberans (DFSP) is a kind of soft tissue sarcoma, mostly occurs in the trunk, followed by proximal extremities and head and neck. Surgical resection is the most important treatment for DFSP, but the local recurrence rate of DFSP is high. Except reported specific chromosomal translocations occurred in DFSP, the association between DNA repair gene mutations and DFSP still unknown. In this report we found a 19-year-old boy with DFSP carries a novel heterozygous germline ERCC2 mutation, which belongs to the nucleotide excision repair (NER) pathway and genetic defects in ERCC2 may contribute to the cancer susceptibility xeroderma pigmentosum (XP), Cocaine syndrome (CS), and trichothiodystrophy (TTD). Different mutations of the ERCC2 gene can lead to diverse diseases, but there are no targeted therapies. In summary, our results enlarged the mutation spectrum of the DFSP patients. It also provides new insights into genetic counseling and targeted therapeutic strategies for patients with DFSP.